Impact of Kenyan New Labour Laws on Gender Disparities in Industrial Occupations in Kenyan Organizations and the Respective Trade Unions - Jamleck, Denis Muchangi; Kerre, Francis; Kalei, Anne; Irungu, Dancan Njagi (International Journal of Economics, Commerce and Management, 2015)
While gender responsive laws and policies have been adapted and enacted, gender differences continue to persist in the various dimensions of industrial occupations both in Kenya and other parts of the world. The objective of this study was to identify the levels of gender representation at the organizational and trade unions level and the impact of the new labour laws on gender disparities of the selected organizations and the related trade unions in Kenya. The study used the descriptive survey research design to obtain data from the selected organizations and the related trade unions. Primary data were obtained from 360 respondents drawn from operational, management and trade unions levels using interviews and questionnaires, while organizations’ records were used for secondary data. Data were summarized using percentages, ratios, frequencies and the measures of central tendency. The findings revealed that gender disparities continue to persist in Kenyan organizations, and that many of the gender responsive policies within the new labour laws lack the capacity to create gender balances in organizations. The key recommendations made included the enforcement of the two third rule at all organizational levels
Keywords: Gender Disparities; Industrial Occupations; Gender Discrimination; New Labour Laws